LinkedSV for detection of mosaic structural variants from linked-read exome and genome sequencing data - Li Fang; Charlly Kao; Michael V. Gonzalez; Fernanda A. Mafra; Renata Pellegrino da Silva; Mingyao Li; Sören-Sebastian Wenzel; Katharina Wimmer; Hakon Hakonarson; Kai Wang (Nature Communications, 2019)
Compared to single nucleotide variants and short indels, structural variants (SVs) are often more challenging to detect using high-throughput sequencing based methods. Here, the authors develop LinkedSV, a computational tool for SV detection using linked-read exome and genome sequencing data.